2022
DOI: 10.1073/pnas.2104453119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hv1 proton channels in myeloid-derived suppressor cells (MDSC) and its potential role in T cell regulation

Abstract: Significance Immunosuppression by myeloid-derived suppressor cells (MDSC), especially near tumor surfaces, involves the extracellular production of reactive oxygen species (ROS). ROS generation in MDSC occurs during the oxidation of NADPH to NADP+, which NOX2 catalyzes. ROS react with the T cell receptor complex, abolishing the antigen presentation, which blocks the immune system elimination of the tumor cells. Extrusion of protons from MDSC by voltage-gated proton channel (H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 61 publications
4
24
0
Order By: Relevance
“…Our study, for the first time, detected within a tumor a high number of Hv1 + myeloid cells that are consistent with the cell surface maker phenotype of PMN- and Mo-MDSCs (see above). Our electrophysiology results are consistent with the data described for in vitro produced MDSCs where Hv1 H + currents of similar magnitude (between 200 pA and 1 nA at +130 mV) to our study were reported using patch-clamp in a mixed MDSC population [ 21 ]. The MDSCs used by Alvear-Arias et al were obtained by induction of the differentiation of bone marrow-derived myeloid precursors by GM-CSF [ 21 ] whereas in our study, MDSCs were isolated directly from LLC tumors induced in mice.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study, for the first time, detected within a tumor a high number of Hv1 + myeloid cells that are consistent with the cell surface maker phenotype of PMN- and Mo-MDSCs (see above). Our electrophysiology results are consistent with the data described for in vitro produced MDSCs where Hv1 H + currents of similar magnitude (between 200 pA and 1 nA at +130 mV) to our study were reported using patch-clamp in a mixed MDSC population [ 21 ]. The MDSCs used by Alvear-Arias et al were obtained by induction of the differentiation of bone marrow-derived myeloid precursors by GM-CSF [ 21 ] whereas in our study, MDSCs were isolated directly from LLC tumors induced in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Second, the whole-cell currents in both MDSC types were sensitive to the pH gradient across the membrane and the membrane potential. The threshold voltage for the activation of the currents shifts along the voltage axis when changing ΔpH, ~40 mV per unit change in the extracellular pH, closely mirroring what has already been described for proton currents in various cells [ 43 , 62 ] including bone-marrow-derived MDSCs [ 21 ]. On the other hand, V thr of the current varies among different cell types [ 42 , 63 ].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations